SAT0112 Prevalence and incidence over 3 years of different comorbidities in rheumatoid arthritis (RA): a 3 year longitudinal study in 769 established ra patients. (15th June 2017) - Gossec, L; Soubrier, M; Foissac, F; Fayet, F; Balandraud, N; Bardin, T; Beauvais, C; Chales, G; Chary-Valckenaere, I; Dernis, E; Euller-Ziegler, L; Flipo, R-M; et al.
Abstract : Background: Comorbidities including cardiovascular (CV) risk, cancer and osteoporosis are frequent in RA.[1] Objectives: To quantify at baseline and 3 years later, the prevalence (at baseline) and incidence (over 3 years) of some selected comorbidities. Methods: This was an open long term (3 years) extension of the COMEDRA 6-month randomized controlled trial in which patients with definite, stable RA were visiting a nurse for comorbidity counselling.[2] Comorbidity status was assessed through face-to-face interviews and nurses provided advice on screening and management, at baseline and 3 years later. The frequency of comorbidities was assessed at both timepoints and incidence of new cases was assessed as overall % of patients and as relative increase in the given comorbidity. Results: Of the 970 recruited patients, 776 (80%) were followed up at 2–4 years (15, 1.5%, had died) and 769 (79%) had available data for comorbidities at both timepoints: at baseline, mean (±SD) age 58 (±11) years, mean disease duration 14 (±10) years; 614 (80%) were women and 538 (70%) were receiving a biologic with a mean DAS28 of 3.1±1.3. At baseline, the most frequent comorbidities were history of fracture (31.9%) and high blood pressure (30.9%) and at 3 years the comorbidity which had most increased (i.e., incidence) in this population aged around 60 years, was high blood pressure (4%) whereas smoking had decreased (Table). Conclusions: Comorbidities are frequent in RA though screening does not always address the most frequent or severe comorbidities. Efforts must be pursued to improve comorbidity screening and prevention. References: Ref 1. Baillet A, Gossec L et al. Ann Rheum Dis. 2016;75(6):965–73. Ref 2. Dougados M, Soubrier M, et al. Ann Rheum Dis. 2015;74(9):1725–33. Acknowledgements: grant from Roche France and from the French National Research Program (PHRC AOM 12072). Disclosure of Interest: None declared